P336 Can Mesenchymal Stem Cell (MSC) apoptosis be used as a biomarker for treatment success in perianal fistulising Crohn's Disease (pCD)? Findings from a prospective pilot study. (21st January 2022) - Iqbal, N; Constable, L; Tozer, P; Lung, P; Hart, A; Powell, N
Abstract: Background: Mesenchymal Stem Cells (MSC) demonstrated promising results in patients with refractory perianal fistulising Crohn's Disease (pCD) in the ADMIRE-CD trial, however their use is limited by treatment cost. Studies of Graft vs. Host Disease (GvHD) patients receiving MSCs for steroid refractory disease have shown that in vitro Peripheral Blood Mononuclear Cell (PBMC) induced MSC apoptosis correlates with clinical response. We conducted a pilot prospective study to investigate the clinical and radiological outcome of MSC treatment and determine whether in vitro MSC apoptosis correlates with clinical response in patients with pCD. Methods: Patient eligibility and MSC administration mirrored that in ADMIRE-CD. Prior to treatment, patient PBMCs were isolated and co-cultured with MSCs and the proportion of apoptotic MSCs identified using flow cytometry (Annexin V+, 7AAD- MSCs). Patients were followed up at, 6-monthly intervals and clinical indices including the Perianal Disease Activity Index (PDAI) and Fistula Drainage Assessment (FDA) were recorded in addition to MRI response. Clinical response categories were determined according to ADMIRE-CD as well as new criteria accounting for radiological healing (Table 1). Results: Ten patients underwent MSC treatment (M=4, median age, 35, range, 22–73 years). At final follow up (median, 24 months, range, 18–30 months), there was a significant improvement in mean FDA (baseline, 1.3, final follow up, 0.5, p<0.01) but not in PDAI. The apoptosis assay was performed in, 9 patients. A greater proportion of MSC apoptosis was demonstrated when co-cultured with pCD patient PBMCs than with PBMCs from healthy controls (Figure, 1). Patients with a percentage of apoptotic MSCs greater than the group median (22.3%) were classed as apoptosis high . At final follow up, apoptosis high patients were also those who demonstrated a response to MSC treatment according to both St Mark's (Figure, 2) and ADMIRE CD criteria (Figure 3). Conclusion: The ability of patient PBMCs to induce the highest proportions of MSC apoptosis correlates with clinical response to MSC treatment in this small sample of patients. An adequately powered prospective study is required to determine the potential use of MSC apoptosis as a biomarker of clinical response.